2014
DOI: 10.1097/ppo.0000000000000018
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-blind, 2-Period, Placebo-Controlled Crossover Trial of a Sustained-Release Methylphenidate in the Treatment of Fatigue in Cancer Patients

Abstract: Purpose This study assessed the efficacy of methylphenidate versus placebo for cancer-related fatigue reduction. Other objectives were to analyze cytokine levels and to determine the effects of methylphenidate on other symptoms, cognitive function, work yield, and patients’ perceptions, and preferences. Methods Patients were randomly assigned (1:1) to receive methylphenidate-placebo or placebo-methylphenidate for 4 weeks. Patients crossed over after 2 weeks. Wilcoxon signed-rank tests and McNemar tests were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(47 citation statements)
references
References 18 publications
(19 reference statements)
2
44
0
1
Order By: Relevance
“…Although classical stimulant medications that increase DA release and/or block DA reuptake increase motivation in rodent models Yohn et al, 2015), they have demonstrated only limited efficacy in chronically treating fatigue and other DA-related symptoms in trials for patients with cancer and other medical illnesses that are associated with inflammation (Bruera et al, 2013;Butler et al, 2007;Escalante et al, 2014;Gong et al, 2014;Mar Fan et al, 2008;Moraska et al, 2010;Pucci et al, 2007;Ruddy et As stimulants act to increase DA release and block DAT function to increase synaptic levels of available DA, these drugs may not provide long-term efficacy in the context of inflammation. As described in detail in the section 'Mechanisms of inflammation effects on dopamine synthesis and release' above, although some evidence exists that inflammation may reduce DA packaging and/or release, and decrease DA receptor signaling, the primary mechanism by which inflammation may impact DA transmission is by decreasing DA synthesis, which would lend to only a limited supply of available vesicular or cytosolic DA on which stimulants may act.…”
Section: Potential Therapeutic Targets For Inflammation Effects On Damentioning
confidence: 99%
“…Although classical stimulant medications that increase DA release and/or block DA reuptake increase motivation in rodent models Yohn et al, 2015), they have demonstrated only limited efficacy in chronically treating fatigue and other DA-related symptoms in trials for patients with cancer and other medical illnesses that are associated with inflammation (Bruera et al, 2013;Butler et al, 2007;Escalante et al, 2014;Gong et al, 2014;Mar Fan et al, 2008;Moraska et al, 2010;Pucci et al, 2007;Ruddy et As stimulants act to increase DA release and block DAT function to increase synaptic levels of available DA, these drugs may not provide long-term efficacy in the context of inflammation. As described in detail in the section 'Mechanisms of inflammation effects on dopamine synthesis and release' above, although some evidence exists that inflammation may reduce DA packaging and/or release, and decrease DA receptor signaling, the primary mechanism by which inflammation may impact DA transmission is by decreasing DA synthesis, which would lend to only a limited supply of available vesicular or cytosolic DA on which stimulants may act.…”
Section: Potential Therapeutic Targets For Inflammation Effects On Damentioning
confidence: 99%
“…For example, neuro-stimulants are frequently used to improve fatigue, attention, and memory [22][23][24]. However, rehabilitation and palliative care approaches to cognitive problems may differ depending upon a host of factors including professional training, familiarity with the patient population, and scientific evidence base [25][26][27][28].…”
mentioning
confidence: 99%
“…Two small studies evaluated the impact of natural restorative environmental intervention on cognitive function in patients with breast cancer (Cimprich, 1993;Cimprich & Ronis, 2003). One study used a pre-and • Natural restorative environmental (Cimprich, 1993;Cimprich & Ronis, 2003) • Qigong (Oh et al, 2012) • Structured rehabilitation (Rottmann et al, 2012) • Vitamin E (Chan et al, 2004;Jatoi et al, 2005) • Pharmacologic approaches -Methylphenidate (Bruera et al, 1992;Butler et al, 2007;Escalante et al, 2014;Gagnon et al, 2005;Gehring et al, 2012;Gong et al, 2014;Lower et al, 2009;Mar Fan et al, 2008;Meyers et al, 1998;Schwartz et al, 2002 Both studies noted improvements in the capacity to direct attention for patients prior to adjuvant therapy. Further research is needed to explore its effect on cognitive function after cancer treatment.…”
Section: Databases: Cinahl ® Pubmed and Cochrane Collaborationmentioning
confidence: 96%
“…Nine empirical studies (Bruera, Miller, Macmillan, & Kuehn, 1992;Butler et al, 2007;Escalante et al, 2014;Gagnon, Low, & Schreier, 2005;Gehring et al, 2012;Lower et al, 2009;Mar Fan et al, 2008;Meyers, Weitzner, Valentine, & Levin, 1998;Schwartz et al, 2002), one literature review that focused on methylphenidate in palliative care (Stone & Minton, 2011), and one meta-analysis that included two empirical studies (Gong et al, 2014) have been conducted with equivocal results as to whether the stimulants improve cognitive impairment in cancer survivors. Three studies examined the use of methylphenidate in patients with advanced cancer and demonstrated improvement in subjective reports of alertness and objective measures of attention, memory, executive functioning, and psychomotor function; however, only one (Bruera et al, 1992) of the studies was a randomized, controlled trial, and all had small sample sizes ranging from 14-30 (Gagnon et al, 2005;Meyers et al, 1998).…”
Section: Databases: Cinahl ® Pubmed and Cochrane Collaborationmentioning
confidence: 97%